Simulation Study on Natural Attenuation of Nitrobenzene in Natural Water - Liu, Baolin; Hua, Xiuyi; Dong, Deming; Li, Ming (Asian Journal of Chemistry, 2012)
This work reports the different aspects of nitrobenzene attenuated in natural water environments under the typical experimental conditions. We usd computer to fit the total reaction rate constants and that in all the aspects and compared between the box model fitting results and experimental results. We analyzed the major fate of nitrobenzene in natural water environments. Studies have shown that the major fate of nitrobenzene in simulated natural water was adsorption, in contrast to adsorption, photodegradation predominanted in the process, followed by evaporation and desorption and compared to other attenuation, the biodegradation process was relatively slow and did not play a leading role.